Impending Atypical Femoral Fracture in a Patient of Breast Cancer With Bone Metastases Receiving Long-term Denosumab. (May 2018) - Sugihara, Tsutomu; Koizumi, Mitsuru; Hayakawa, Keiko; Ito, Yoshinori; Sata, Naohiro
Abstract : Abstract: Atypical femoral fractures (AFFs) occur in both osteoporosis patients and cancer patients who receive long-term bisphosphonate treatment. Denosumab offers an alternative approach for the treatment of bone metastases. We describe a 59-year-old woman with a history of breast carcinoma and bone metastasis who was prescribed denosumab for 4 years. The patient had no history of any prior bisphosphonate use. Bone scintigraphy showed an abnormal uptake in the right femur, which was confirmed as an impending AFF or atypical femoral stress reaction. In oncological patients receiving long-term denosumab, AFF should be included as a differential diagnosis for focal femoral findings.